Enhanced CHO Clone Screening: Application of Targeted Locus Amplification and Next‐Generation Sequencing Technologies for Cell Line Development. Issue 7 (15th May 2019) - Aeschlimann, Samuel H.; Graf, Christian; Mayilo, Dmytro; Lindecker, Hélène; Urda, Lorena; Kappes, Nora; Burr, Alicia Leone; Simonis, Marieke; Splinter, Erik; van Min, Max; Laux, Holger
Abstract : Early analytical clone screening is important during Chinese hamster ovary (CHO) cell line development of biotherapeutic proteins to select a clonally derived cell line with most favorable stability and product quality. Sensitive sequence confirmation methods using mass spectrometry have limitations in throughput and turnaround time. Next‐generation sequencing (NGS) technologies emerged as alternatives for CHO clone analytics. We report an efficient NGS workflow applying the targeted locus amplification (TLA) strategy for genomic screening of antibody expressing CHO clones. In contrast to previously reported RNA sequencing approaches, TLA allows for targeted sequencing of genomic integrated transgenic DNA without prior locus information, robust detection of single‐nucleotide variants (SNVs) and transgenic rearrangements. During clone selection, TLA/NGS revealed CHO clones with high‐level SNVs within the antibody gene and we report in another case the utility of TLA/NGS to identify rearrangements at transgenic DNA level. We also determined detection limits for SNVs calling and the potential to identify clone contaminations by TLA/NGS. TLA/NGS also allows to identify genetically identical clones. In summary, we demonstrate that TLA/NGS is a robust screening method useful for routine clone analytics during cell line development with the potential to process up to 24 CHO clones in less than 7 workdays. Abstract : Targeted locus amplification (TLA) and next‐generation sequencing (NGS) empower Chinese hamster ovary (CHO) clone selection for biotherapeutic antibody production. TLA presents a high‐quality, rapid, and high‐throughput method to select clones with most favorable product quality. In different case studies, the utility of TLA/NGS for CHO cell line development of biotherapeutic proteins are reported.